RECONSTRUCTING THE LEGISLATIVE ELECTORAL SYSTEM: ENHANCING THE QUALITY OF THE DPR THROUGH A CLOSED PROPORTIONAL SYSTEM - John Kenedy Azis; Bintan R. Saragih; Tri Sulistyowati (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2025)
This study proposed a reform of Indonesia’s legislative electoral system by implementing a closed proportional model to improve the quality and effectiveness of the House of Representatives (DPR). The open proportional system, standed since the 1998 Reform Era, has raised several serious issues, including the prevalence of money politics, high nomination costs, weakened party cohesion, and reduced accountability of elected representatives. Based on theoretical approaches encompassing popular sovereignty, political representation, and party systems which supported by empirical data, this study argues that a closed system aligns more closely with the principles of substantive democracy. The research proposed a closed-list system rooted in meritocracy and accountability, emphasizing objective candidate recruitment, independent oversight, a minimum 30 percent quota for women, and public monitoring of candidate lists. This reform is recommended to be implemented through a revision and integration of various electoral laws within an omnibus law framework. Conceptually, the findings contribute to the development of constitutional law and the strengthening of representative institutions that are professional, transparent, and people-oriented.